2010
DOI: 10.1007/s10059-010-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Root Hair-Specific EXPANSIN B Genes Have Been Selected for Graminaceae Root Hairs

Abstract: Cell differentiation ultimately relies on the regulation of cell type-specific genes. For a root hair cell to undergo morphogenesis, diverse cellular processes including cell-wall loosening must occur in a root hair cell-specific manner. Previously, we identified and characterized root hairspecific cis-elements (RHE) from the genes encoding the cell wall-loosening protein EXPANSIN A (EXPA) which functions preferentially on dicot cell walls. This study reports two root hair-specific grass EXPB genes that contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Three expansins, which are encoded by HvEXPB1 (Kwasniewski and Szarejko, 2006), OsEXPB5, and OsEXPA17 (Won et al, 2010;ZhiMing et al, 2011), have been proven to be involved in RH initiation and elongation. Mutant analysis showed that the HvEXPB1 transcript is present in the root but not in the shoot (Kwasniewski and Szarejko, 2006).…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three expansins, which are encoded by HvEXPB1 (Kwasniewski and Szarejko, 2006), OsEXPB5, and OsEXPA17 (Won et al, 2010;ZhiMing et al, 2011), have been proven to be involved in RH initiation and elongation. Mutant analysis showed that the HvEXPB1 transcript is present in the root but not in the shoot (Kwasniewski and Szarejko, 2006).…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongationmentioning
confidence: 99%
“…elongation (Won et al, 2010). A rice line that produced RHs that were 70% shorter than those of the wild type has been shown to harbor a single nucleotide variant for OsEXPA17.…”
Section: "Tis Within Ourselves That We Are Thus or Thus": Elongationmentioning
confidence: 99%
“…The quantification of PM-localized PIN:GFP signals was performed using the histogram function of Adobe Photoshop (Won et al, 2010). For the root gravitropism assay, light-grown 3-d-old seedlings were turned 90°in Figure 3A and 135°in Figure 3B for 12 h in the dark before observing root bending.…”
Section: Measurement Of Biological Factors and Observation Of Reportementioning
confidence: 99%
“…Many functional orthologs of AtEXPA7 (i.e., EXPA-like genes exhibiting root hair-specific expression) have been identified experimentally among monocots and eudicots (Kim et al, 2006). Recently, we identified two root hair-specific EXPBs in rice and barley (Won et al, 2010). These genes encode proteins that may be specific for root hair growth in the Poaceae.…”
Section: Introductionmentioning
confidence: 99%